LEARNING PROCEEDING SPLINE TECHNIQUES WITH A ALLUSION OF PARTIAL DIFFERENTIAL EQUATIONS - Ramehar; Rupender Singh (Galaxy International Interdisciplinary Research Journal, 2021)
In the modern era, fractional order differential equations have gained a significant amount of research work due to their wide range of applications in various branches of science and engineering such as physics, electrical networks, fluid mechanics, control theory, theory of Viscoelasticity, neurology, and theory of electromagnetic acoustics.The spline approximation techniques have been applied extensively for numerical solution of ODEs and PDEs. The spline functions have a variety of significant gains over finite difference schemes. These functions provide a continuous differentiable estimation to solution over the whole spatial domain with great accuracy. The straightforward employment of spline functions provides a solid ground for applying them in the context of numerical approximations for initial/boundary problems.